Behavior Modification Techniques to Build Student Discipline - Abidah, Lani; Thohir, Mohamad; Syaputra, Yogi Damai (Program Studi Bimbingan dan Konseling Islam, 2024)
Discipline is a fundamental value in education that has a significant influence on student learning achievement and character development. Obedience, compliance, and orderliness, which are important aspects of an individual's personality in the family, school, and community environments, are reflected in discipline. However, there are still challenges with low student discipline, which is influenced by various internal and external factors. The role of guidance and counseling (BK) teachers is vital in providing motivation through appropriate counseling services. An effective discipline management program includes planning, implementation, evaluation, and consistency from all parties involved. This study aims to identify the programs implemented by the BK teacher team at SMPN 13 Surabaya to build student discipline, as well as the behavior modification techniques applied. With a descriptive qualitative approach involving interviews, observations, and document analysis, this study found that the programs implemented include morning greetings, collecting cellphones in the BK room, congregational prayers, and participation in Sekolah Arek Suroboyo. Behavior modification techniques applied include positive reinforcement, token economy, and negative reinforcement. This research enhances our understanding of effective strategies for managing student discipline through behavior modification, and provides a model that other schools can implement.